Scanning Auger Microscopy Studies of Silane Films Grown on Plasma-Modified HOPG Surfaces - Taylor JK; Wiese JR; Harmer SL; Quinton JS (MDPI (Basel, Switzerland), 2019)
The growth of silane films on plasma oxidized highly oriented pyrolytic graphite (HOPG) surfaces has been studied using wet chemical deposition of propyltrimethoxysilane (PTMS) and propyldimethylmethoxysilane (PDMMS). Scanning Auger microscopy (SAM) and X-ray photoelectron spectroscopy (XPS) were used to investigate the chemical composition and morphology of the silane films. The effects of several deposition parameters were examined, including the necessity of oxidation of the HOPG surface, addition of water with the silane, and rinsing before curing. The optimal conditions needed to create a complete uniform film differ for the two silanes due to differences in their structures. Both silanes require an oxidized HOPG surface for a film to grow, the addition of water with PTMS results in a thicker film, while the addition of water with PDMMS decreases the film growth. Rinsing of both samples before curing removes physisorbed species, leaving only the covalently bonded film on the surface.
Keywords: HOPG; PDMMS; PTMS; SAM; XPS; carbon; graphite; plasma; silane